Analisis Pendapatan dan Tingkat Kesejahteraan Rumah Tangga Nelayan Tradisional di Desa Bunutan Kecamatan Abang Kabupaten Karangasem - PRADNYANA, I KOMANG GEDE ROBBIE; RANTAU, I KETUT; ANGGRENI, I GUSTI AYU AGUNG LIES (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.10, No.2, Desember 2021, 2021)
Analysis of Income and Welfare Level of Fishermen Households in Bunutan Village, Abang District, Karangasem Regency This research was to know (1) The income obtained by traditional fishermen from fish catches, and the income of traditional fishermen’s households, (2) The level of welfare of traditional fishermen households, and (3) Factors influenced the welfare level of traditional fishermen households in Bunutan Village.This study was conducted in Bunutan Village, Abang District, Karangasem Regency with survey method. Respondents in this study were 50 traditional fishermen who used netfishes whom selected using simple random sampling method. Household income consists of on farm, off farm and non fishing. Household welfare level is analyzed by Central agency on Statistics 2018 criteria. The factors that influence household welfare analyzed by binary logistic regression. The results showed that the income obtained by fishermen from fish catches in the western season was Rp Rp4.823.677, in the eastem season was Rp13.663.463, and in the normal season was Rp8.505.180. The contribution of fish catches income (on farm) was 91.01 percent traditional fishermen households income, the contribution of bussines income in the agricultural sector outside the fish catches (off farm) was 5.55 percent, and the contribution of business outside the agricultural sector (non fishing) was 3.60 percent. The households of traditional fishermen as big as 52,00 percent were classified as not prosperous yet and 48,00 percent were prosperous based on criteria of walfare according to Central agency on Statistics 2018. The factors influenced the welfare of traditional fishermen households were the level of education and income of fishermen’s households.